Pengaruh Promosi Media Sosial Instagram Terhadap Tahap Keputusan Pembelian Produk Lorong Kopi Cilandak di Jakarta Selatan - Shaddat, Arnold; Maudiarti, Santi; Pramanik, Purwanti Dyah (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan Digital, 2026)
This study aims to examine the effect of Instagram social media promotion on consumers' purchasing decisions at Lorong Kopi Cilandak, South Jakarta. The rapid growth of social media has encouraged coffee shops to utilize Instagram as a digital marketing platform to enhance product attractiveness and build stronger relationships with consumers. This study employed a quantitative approach using a survey method. The study population consisted of followers of the @temanlorong Instagram account, while the sample was determined using the Slovin formula and a convenience sampling technique. Data were collected through a questionnaire using a five-point Likert scale. The Instagram social media promotion variable was measured using the dimensions of content creation, content sharing, connecting, and community building, whereas the purchasing decision variable was measured based on the stages of need recognition, information search, alternative evaluation, purchase decision, and post-purchase behavior. Data were analyzed using validity, reliability, and hypothesis testing. The results indicate that all research instruments met the validity and reliability requirements. Furthermore, Instagram social media promotion was found to have a positive and significant effect on consumers' purchasing decisions. These findings suggest that Instagram is an effective digital marketing platform for influencing consumers' purchasing decisions in the coffee shop industry. Keywords: Instagram social media promotion, purchasing decision